Afterword: Dispossession with Possession, Governance with Colonialism: Algonquian Hunting Territories and Anthropology as Engaged Practice - Feit, Harvey A. (Anthropologica, 2018)
Hunting territories have been and remain central to struggles of northern Algonquian peoples for governance of their lands, to the changes they envision, and for the responses they make when others enter their lands. Hunting territories are also envisioned by some nation-state governments and resource developers as means to disrupt Indigenous governance, communities and tenures to facilitate colonial regimes of control. What happened in this region, and how it came to be understood, has been part of the development of broad anthropological understandings of how peoples can continue living and actively governing their lands amidst colonial intrusions and relations. The anthropology of Algonquian hunting territories has throughout the last century been closely linked to several theoretical debates and to diverse anti-colonial analyses, both within and outside the discipline. Anthropologists’ work has involved ever-changing relationships with northern Algonquian peoples and with the beyond-colonising movements, challenges and agreements they have initiated. These relationships have involved long-term anthropological engagements and practices that continue to be taken up in debates about anthropological scholarship and activism. The articles in this volume substantially update these northern Algonquian–state–market–anthropology relations and the analyses of Algonquian hunting territories.